Dialogue Journal on Student Writing in the EFL Classroom - Surdyanto, Annas (CV. Pena Persada, 2018)
The article presents critical review of three empirical studies on the use of dialogue journal in the EFL classroom. Results of those studies are supportive to integrate dialogue journal into the EFL classroom. The results of the studies also confirm that using dialogue journal can improve writing performance. Besides, it is also useful to reduce writing apprehension. The critical review suggested that procedure of using journal should be more thoroughly followed. In the context of Indonesian EFL classroom, there is little information concerning on the use of dialogue journal.